P2O5-mediated Friedel-Crafts acylation of activated arenes with carboxylic acid as acylating agent - Kalshetti, Rupali G.; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
P2O5 has been found to be a highly efficient and environmental friendly catalyst for the liquid-phase acylation of activated aromatic substrates giving aromatic ketones (45-93%) in a regioselective manner. Both aromatic and aliphatic carboxylic acids can be employed as acylating source. The process is particularly demonstrated at 100 g scale in the case of anisole and acetic acid to produce 4-methoxyacetophenone.
Keywords: 4-methoxyacetophenone; Carboxylic acid; Friedel-Crafts acylations; phosphorus pentoxide